Moringa oleifera (Lam) LEAF: A RARE PROTEIN SOURCE FOR NILE TILAPIA (Oreochromis niloticus) FINGERLINGS - NWANKPA, K.I. (Nigerian Journal of Fisheries, 2016)
The study examined the effects of the varying levels of Moringa oleifera leaf meal diets on the growth performance, survival rate and nutrient utilization of O.niloticus fingerlings for a period of 90 days. Moringa oleifera leaf meal diets substituted soybean at 0 %( control), 5%, 10% and 15%. A total number of 180 O.niloticus fingerlings of mean weight 2.43+ 0.22g were randomly distributed into twelve transparent plastic tanks at 15 fish per tank in triplicate treatment and fed twice daily for 90 days. The mean weight gained (MWG), specific growth rate (SGR), average daily gain (ADG),survival rate (SR),feed intake(FI),feed conversion ratio(FCR),protein efficiency ratio(PER),protein gain (PG),protein production value (PPV) and carcass chemical composition(CCC) were calculated. The results obtained from this study showed that M.oleifera leaf meal can be used to substitute soybean up to 10% level in tilapia feed formulation without any probable effect on the growth parameters and nutrient utilization. Furthermore, the higher survival rate of fish fed M.oleifera leaf meal brings to bear the efficacy of the abundant minerals and antimicrobial properties inherent in the leaf, which is readily available and affordable than the highly competed for and expensive soybean.